Oriented Assembly of 2D Metal-Pyridylporphyrinic Framework Films for Giant Nonlinear Optical Limiting - Li, De-Jing; Li, Qiao-hong; Gu, Zhi-Gang; Zhang, Jian (Nano letters, 2021)
The development of metal-organic frameworks (MOFs) with nonlinear optical (NLO) properties is of pronounced significance for optical devices. Herein, a series of 2D MOFs ZnTPyP(M) (TPyP = 5,10,15,20-tetrakis(4-pyridyl)porphyrin, M = Cu, Ni, Mn, H ) films with [010]-orientation growth composed of ultrathin nanosheets from a pyridylporphyrinic ligand are first obtained by using a liquid-phase epitaxial (LPE) layer-by-layer (lbl) growth approach. ZnTPyP(M) films show a giant nonlinear optical limiting (OL) response and can be modulated by tuning the type of metalloporphyrinic ligands. As a result, ZnTPyP(Cu) film exhibits the highest nonlinear absorption coefficient of 5.7 × 10 m/W compared to other reported NLO materials. Density functional theory calculations were consistent with the experimental results, revealing that the tunable π-π* local excitation and the increased delocalization of the metalloporphyrinic group regulate the NLO performance of ZnTPyP(M) films. These findings provide new insight into the effect of 2D porphyrinic MOFs toward the NLO response and offer new film candidates for nonlinear OL application.